Is the IMF in ellipticals bottom-heavy?: Clues from their chemical abundances - De Masi, Carlo Maria; Rosani, Giulio; Pasquali, Anna (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We tested the implementation of different initial mass functions (IMFs) in our model for the chemical evolution of ellipticals, with the aim of repro
Gesehen am 09.01.2019
Advance access publication 2018 November 22